MERENCANAKAN PROGRAM PENGAJARAN DENGAN PENDEKATAN FUNCTIONAL GRAMMAR (TOPIK: FOOD) - Tuti Purwati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2011)
This article explain about Planning the Instructional Program for the teachers of elementary School, especially English teacher. The purpose of this program is for giving procedure genre matter with topic on food. The functional grammar focused on discourse analyze, in where every discourse has genre. This discourse can be introduced to the beginner students of foreign language. In this case, English is instructed with appropriate method and model. Focus of attention in this paper is four level of instructional process are build context, make model, composite and free construction. Key words: genre, functional grammar, food